Postcolonialism and translation: the dialectic between theory and practice - Bandia, Paul F. (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Postcolonial intercultural writing has been likened to translation both in terms of the writing practice and the nature of the postcolonial text, which often involves multiple linguistic and cultural systems. To highlight the significance of this view of translation as a metaphor for postcolonial writing and its impact on current translation theory, this paper attempts to lay the groundwork for defining the linguistic and cultural status of postcolonial discourse and to establish parallels between the translation process and some strategies for crafting the postcolonial text. The ontological relation between translation theory and practice is discussed in the light of post- colonial translation practices which have broadened the scope of research in translation studies to include issues of ideology, identity, power relations, and other ethnographic and sociologically based modes of investigation.